Polarizing plate and method for manufacturing the same, and image display device using the same

By forming a polyalkylene part at the end of the polarizer and forming a sealing part, the problem of decolorization of the polarizer in a high temperature and high humidity environment is solved, and excellent optical characteristics and extended service life are achieved.

CN115398287BActive Publication Date: 2025-02-11NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180024461.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-18
Publication Date
2025-02-11
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

The optical characteristics of the existing polarizers are reduced in high temperature and high humidity environments, resulting in discoloration and affecting the performance of the image display device.

Method used

By forming a polyalkylene portion at the end of the polarizer and forming a seal portion around the polyalkylene portion, a polarizing plate is manufactured by laser irradiation or electron beam irradiation heating.

Benefits of technology

It effectively suppresses the decolorization phenomenon of polarizers in high temperature and high humidity environments, maintains excellent optical characteristics, and extends the service life of polarizers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115398287B_ABST
    Figure CN115398287B_ABST
Patent Text Reader

Abstract

A polarizing plate is provided which can maintain excellent optical properties and prevent discoloration even in a high temperature and high humidity environment. The polarizing plate of the present invention is in the form of a sheet, and comprises: a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic substance, and a protective layer disposed on at least one side of the polarizer, wherein a polyene portion is formed at an end of the polarizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing plate and a method for manufacturing the same, and an image display device using the polarizing plate. Background Art

[0002] In image display devices (such as liquid crystal display devices, organic EL display devices, quantum dot display devices), a polarizing plate is arranged on at least one side of the display unit in most cases due to the image forming method. However, the polarizing plate has a problem that the optical properties of the polarizer that substantially dominates the optical properties of the polarizing plate are reduced in durability under high temperature and high humidity environments. More specifically, the polarization performance of the end of the polarizer disappears under high temperature and high humidity environments, and as a result, the so-called discoloration phenomenon sometimes occurs. In recent years, the demand for narrow frame (or so-called frameless depending on the situation) of image display devices has been increasing, and the necessity to prevent discoloration of the ends has increased.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2000-338329 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] The present invention has been made to solve the above-mentioned conventional problems, and its main object is to provide a polarizing plate which can maintain excellent optical properties and prevent discoloration even in a high-temperature and high-humidity environment, and a simple method for producing the same.

[0008] Solutions for solving problems

[0009] The polarizing plate according to the embodiment of the present invention is in a sheet shape and includes a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic substance and a protective layer disposed on at least one side of the polarizer, wherein a polyene portion is formed at an end of the polarizer.

[0010] In one embodiment, the polyolefin part is formed to a position 25 μm or more inward in the plane direction from the outer peripheral edge of the polarizer. In one embodiment, the polyolefin part is formed to a position 1000 μm or less inward in the plane direction from the outer peripheral edge of the polarizer.

[0011] In one embodiment, the polarizing plate has a sealing portion covering an outer peripheral end surface. In one embodiment, the sealing portion is a melt-solidified product of a resin film constituting the protective layer.

[0012] According to another aspect of the present invention, a method for manufacturing the polarizing plate is provided, which comprises: cutting off the end of the polarizing plate by laser irradiation; or, after irradiating the end surface of the polarizing plate with an electron beam, heating the irradiated portion.

[0013] According to another aspect of the present invention, there is provided an image display device comprising: a display unit and the above-mentioned polarizing plate disposed on at least one side of the display unit.

[0014] Effects of the Invention

[0015] According to the embodiment of the present invention, a polyene portion is formed at an end portion of a polarizer, so that a polarizing plate can be provided which can maintain excellent optical properties and prevent discoloration even in a high-temperature and high-humidity environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.

[0017] Figure 2 for Figure 1 Schematic top view of the polarizer of the polarizing plate.

[0018] Figure 3 It is a schematic diagram for explaining the calculation of the decolorization amount. DETAILED DESCRIPTION

[0019] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0020] A. Overall composition of polarizing plate

[0021] Figure 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention; Figure 2 for Figure 1 Schematic top view of a polarizer in a polarizing plate. The polarizing plate 100 is in the form of a sheet, and comprises: a polarizer 10, a first protective layer 20 disposed on one side of the polarizer 10, and a second protective layer 30 disposed on the other side of the polarizer 10. Either the first protective layer 20 or the second protective layer 30 may be omitted depending on the purpose, etc. The polarizer 10 is composed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance (representatively iodine, a dichroic dye). In an embodiment of the present invention, a polyene portion 40 is formed at an end of the polarizer 10.

[0022] The polyene part 40 is a part of the polarizer (substantially a PVA resin) that has been polyene-formed, as the name suggests. More specifically, the polyene part refers to a part of the PVA resin that has three or more double bonds formed by thermal decomposition or the like, which can be determined by the absorption spectrum at 1134 / cm-1 and 1527 / cm -1 The peak appears to confirm. Polyeneization of polarizers will reduce or eliminate the polarization performance, so it is technical common sense in the industry to preferably inhibit or prevent the polyeneization of polarizers. The present inventors have conducted in-depth research on the discoloration of polarizers (ultimately image display devices) in high temperature and high humidity environments, and surprisingly found that by deliberately polyeneizing the polarizers, the discoloration in high temperature and high humidity environments can be significantly inhibited, thereby completing the present invention. As such, the present invention is an invention based on a technical concept in a direction completely opposite to the technical common sense in the industry, and its effect is an unexpected excellent effect obtained through repeated experiments based on such technical concepts.

[0023] The polyene portion 40 is formed from the outer peripheral end of the polarizer 10 to a position of, for example, 25 μm or more. In other words, the width W of the polyene portion is, for example, 25 μm or more. When the width is in such a range, a polarizer in which discoloration in a high temperature and high humidity environment is significantly suppressed can be obtained. The width W of the polyene portion is preferably 50 μm or more, more preferably 100 μm or more, further preferably 150 μm or more, particularly preferably 200 μm or more, and particularly preferably 500 μm or more. On the other hand, from the viewpoint of preventing adverse effects on the optical properties of the polarizer and the display properties of the image display device, the width W of the polyene portion is preferably 1000 μm or less, more preferably 800 μm or less. In this way, by setting the width of the polyene portion to a specified range, a polarizer in which discoloration in a high temperature and high humidity environment is significantly suppressed can be obtained without adversely affecting the optical properties of the polarizer and the display properties of the image display device.

[0024] The monomer transmittance of the polyene portion is preferably 25% to 45%, more preferably 35% to 45%. The polarization degree of the polyene portion is preferably 90% or more, more preferably 98% or more. It is substantially difficult to structurally / quantitatively determine the degree of polyene in the polyene portion, and the monomer transmittance and polarization degree can be indicators of the degree of polyene. That is, the degree of reduction in the polarization performance of the polarizer can be an indicator of the degree of polyene. By adjusting the monomer transmittance and polarization degree of the polyene portion to such a range, a polarizer in which discoloration in a high temperature and high humidity environment is significantly suppressed can be obtained without adversely affecting the optical properties of the polarizer and the display properties of the image display device.

[0025] In one embodiment, a sealing portion 50 covering the outer peripheral end surface may be formed on the polarizing plate 100. By forming the sealing portion, discoloration in a high temperature and high humidity environment can be further suppressed. The sealing portion 50 represents a molten solidified product of the resin film constituting the first protective layer 20 and / or the second protective layer 30. The moisture permeability of the sealing portion is preferably 300 g / m 2 / 24hr or less, more preferably 100g / m2 / 24hr or less, more preferably 50g / m 2 / 24hr or less, particularly preferably 25g / m 2 / 24hr or less. The lower limit of moisture permeability is, for example, 0.01g / m 2 / 24hr, preferably less than the detection limit. When the moisture permeability of the sealing portion 50 is within such a range, the polarizer can be well protected from contact with moisture and oxygen in the air. It should be noted that the moisture permeability can be measured in accordance with JIS Z0208.

[0026] The thickness of the sealing portion 50 is preferably 1 μm to 1000 μm, more preferably 5 μm to 300 μm. In the present specification, the “thickness of the sealing portion” refers to the thickness in the direction extending outward from the outer peripheral end surface of the polarizing plate unless otherwise specified.

[0027] The amount of discoloration of the polarizing plate of the embodiment of the present invention after being kept for 240 hours at 65°C and 90% RH is preferably 100 μm or less, more preferably 50 μm or less, further preferably 40 μm or less, particularly preferably 30 μm or less, and particularly preferably 10 μm or less. The lower limit of the discoloration amount is preferably zero. The amount of discoloration can be calculated, for example, as follows: a test piece of a specified size is cut out from the polarizing plate (or polarizer), and the test piece has two opposite sides in the direction orthogonal to the stretching direction and the stretching direction. It should be noted that the stretching direction is representatively corresponding to the absorption axis direction of the polarizer. The stretching direction may correspond, for example, to the long side direction (conveying direction (MD direction)) of the polarizing plate. Then, the test piece is bonded to an alkali-free glass plate of the same size with an adhesive. It is used as a substitute for an image display device. It should be noted that the liquid crystal display device substitute bonds the visual recognition side test piece and the back side test piece to both sides of the glass plate. The organic EL display device substitute only bonds the visual recognition side test piece to a single side of the glass plate. The image display device substitute was placed in an oven at 65°C and 90% RH for 240 hours for heating and humidification. The discoloration of the ends of the liquid crystal display device substitute after heating and humidification was studied using a microscope. For the organic EL display device substitute, the discoloration of the ends when the heated and humidified organic EL display device substitute was configured in a state of orthogonal polarization (crossed nicol) with a standard polarizing plate was studied using a microscope. In any case, specifically, the size of the discoloration (discoloration amount: μm) from the end of the test piece (polarizing plate or polarizer) was measured. Figure 3As shown, the larger of the discoloration amount a from the end in the stretching direction and the discoloration amount b from the end in the direction perpendicular to the stretching direction is taken as the discoloration amount. It should be noted that the polarization characteristics of the discolored area are significantly low and the function as a polarizer is not substantially exerted. Therefore, the smaller the discoloration amount, the more preferred. According to an embodiment of the present invention, as described above, by intentionally polyeneizing the end of the polarizer, the discoloration after the heating and humidification test can be significantly suppressed. This is an excellent effect that is completely unexpected based on the technical common sense of the industry.

[0028] A-1. Polarizer

[0029] As described above, the polarizer is composed of a PVA-based resin film containing a dichroic substance (representatively iodine or a dichroic dye). The dichroic substance is preferably iodine. The polarizer can be formed of a single-layer resin film or a laminate of two or more layers.

[0030] As a specific example of a polarizer formed by a single-layer resin film, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially acetalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers are subjected to dyeing and stretching treatments based on dichroic substances such as iodine and dichroic dyes, dehydrated products of PVA, dehydrochlorinated products of polyvinyl chloride, and other polyene-based oriented films. Preferably, from the perspective of excellent optical properties, a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching is used. The above-mentioned iodine-based dyeing is performed, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after dyeing or while dyeing. In addition, dyeing can also be performed after stretching. As needed, the PVA film is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water and washing it before dyeing, not only can stains and anti-blocking agents on the surface of the PVA film be washed away, but the PVA film can also be swollen to prevent uneven dyeing.

[0031] As specific examples of polarizers obtained using a laminate, there can be cited: a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, as follows: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, to obtain a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching may also include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in an aqueous boric acid solution, as required. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective film of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective film that meets the purpose can be laminated on the peeling surface for use. The details of the manufacturing method of such a polarizer are described in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. All the records of these publications are cited in this specification as a reference.

[0032] As the PVA resin forming the above-mentioned PVA resin film, any appropriate resin can be used. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be cited. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.9 mol%, and more preferably 99.0 mol% to 99.5 mol%. The saponification degree can be calculated according to JIS K6726-1994. By using a PVA resin with such a saponification degree, a polarizer with excellent durability can be obtained. When the saponification degree is too high, there is a concern that gelation will occur.

[0033] The average degree of polymerization of the PVA-based resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 5000, and more preferably 1500 to 4500. The average degree of polymerization can be determined in accordance with JIS K6726-1994.

[0034] The iodine concentration in the PVA-based resin film (polarizer) is, for example, 5.0% by weight to 12.0% by weight, and the boric acid concentration in the PVA-based resin film is, for example, 12% by weight to 25% by weight.

[0035] The thickness of the polarizer is, for example, 12 μm or less, preferably 8 μm or less, more preferably 7 μm or less, and further preferably 6 μm or less. On the other hand, the thickness of the polarizer is preferably 1 μm or more, and more preferably 2 μm or more.

[0036] The polarizer preferably exhibits absorption dichroism at any wavelength in the range of 380 nm to 780 nm. The monomer transmittance of the polarizer (excluding the polyene portion) is preferably 40.0% to 46.0%, more preferably 40.5% to 43.0%. The polarization degree of the polarizer (excluding the polyene portion) is preferably 99.9% or more, more preferably 99.95% or more, and further preferably 99.98% or more.

[0037] A-2. Protective layer

[0038] The first and second protective layers are formed by any appropriate film that can be used as a protective layer of a polarizer. For specific examples of the material as the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be cited. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic carbamate resins, epoxy resins, silicone resins, etc. can also be cited. In addition, for example, glassy polymers such as siloxane polymers can also be cited. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above resin composition.

[0039] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (outer protective layer) disposed on the opposite side of the display unit is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. It should be noted that, when surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.

[0040] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (inner protective layer) disposed on the display unit side is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 60 μm. In one embodiment, the inner protective layer is preferably optically isotropic. In this specification, "optical isotropy" means that the in-plane phase difference Re (550) is 0 nm to 10 nm, and the phase difference Rth (550) in the thickness direction is -10 nm to + 10 nm. In another embodiment, the inner protective layer is a phase difference layer having any appropriate phase difference value. In this case, the in-plane phase difference Re (550) of the phase difference layer is, for example, 110 nm to 150 nm, and the angle between its slow axis and the absorption axis of the polarizer is, for example, 40° to 50°. "Re(550)" is the in-plane phase difference measured at 23°C with light of wavelength 550nm, and is obtained by the formula: Re = (nx-ny) × d. "Rth(550)" is the phase difference in the thickness direction measured at 23°C with light of wavelength 550nm, and is obtained by the formula: Re = (nx-nz) × d. Here, "nx" is the refractive index in the direction (i.e., the slow axis direction) where the in-plane refractive index is the largest, "ny" is the refractive index in the direction orthogonal to the slow axis (i.e., the fast axis direction) in the plane, "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (film).

[0041] B. Method for manufacturing polarizing plate

[0042] Hereinafter, only the characteristic parts of the method for producing a polarizing plate described in the above section A will be described. Operations and conditions related to the method for producing a polarizing plate that are not described below are well known in the art, and thus detailed descriptions thereof will be omitted.

[0043] In one embodiment, the manufacturing method includes cutting off the end of the polarizing plate by laser irradiation. The end of the polarizing plate is cut off by laser irradiation, thereby forming a polyene portion 40 at the end (i.e., the cut portion), and a sealing portion 50 may also be formed at the same time. In more detail, when the end of the polarizing plate is cut off by laser irradiation, the laser irradiated portion of the polarizer is thermally decomposed to form a polyene. The laser irradiated portion exists in both the cut portion of the polarizer and the polarizer remaining after cutting. The end of the polarizer remaining after cutting becomes the laser irradiated portion, so a polyene portion is formed at the end of the polarizer. At the same time, the protective layer of the irradiated portion (substantially the resin film constituting the protective layer) is melted by laser irradiation, and the molten resin flows to cover the end face of the polarizing plate, and then solidifies. As a result, a sealing portion composed of a molten solidified product of the resin film constituting the protective layer is formed.

[0044] As a laser light source that can be used in laser irradiation, for example, an infrared laser including a CO2 laser light source having an oscillating laser wavelength of 9 μm to 11 μm in the infrared region can be cited. Infrared lasers can easily obtain a power of several 10W, and further, the polarizing plate (substantially a polarizer) can be effectively heated by molecular vibrations accompanying infrared absorption, thereby enabling etching accompanied by a phase change of the substance. As another example of a laser light source that can be used in laser irradiation, a CO laser light source having an oscillating laser wavelength of approximately 5 μm can be cited. As yet another example of a laser light source, near infrared (NIR), visible light (Vis) and ultraviolet (UV) pulse laser light sources can be cited. As NIR, Vis and UV pulsed laser light sources, examples include those with an oscillating laser wavelength of 1064nm, 532nm, 355nm, 349nm or 266nm (higher harmonics of a solid laser light source using Nd:YAG, Nd:YLF or YVO4 as the medium), an excimer laser light source with an oscillating laser wavelength of 351nm, 248nm, 222nm, 193nm or 157nm, and an F2 laser light source with an oscillating laser wavelength of 157nm.

[0045] As the oscillation form of the laser light source, pulse oscillation is preferred over continuous wave (CW) oscillation from the viewpoint of suppressing excessive thermal damage to the polarizer. The pulse width can be between 10 femtoseconds (10 -14 seconds) to 1 millisecond (10 -3 The laser beam can be appropriately set within the range of 100 to 200 s. It is also possible to set more than two pulse widths for processing. There is no restriction on the polarization state of the laser, and linear polarization, circular polarization, and random polarization can be applied. There is no restriction on the spatial intensity distribution of the laser. It is preferred to use a Gaussian beam that exhibits good light collection, can achieve small points, and can expect increased productivity. It can also be shaped into a flat-top beam using a diffractive optical element or the like.

[0046] The irradiation conditions of the laser can be set to any appropriate conditions. For example, when using a CO2 laser, the pulse energy is preferably 2.67mJ to 6.67mJ, and more preferably 4.00mJ to 6.00mJ. The scanning speed is preferably 100mm / sec to 1000mm / sec, and more preferably 250mm / sec to 700mm / sec. The repetition frequency is, for example, 5kHz to 30Hz. The input energy of the pulsed laser is preferably 80000μJ / mm to 200000μJ / mm, and more preferably 120000μJ / mm to 180000μJ / mm. It should be noted that the input energy E (μJ / mm) is calculated according to the following formula.

[0047] E=(e×M) / (V)

[0048] e: Pulse energy (J)

[0049] M: repetition frequency (Hz)

[0050] V: Scanning speed (mm / sec)

[0051] The irradiation form (scanning pattern) of the laser light can be appropriately set according to the purpose. For example, the laser light can be scanned in a straight line, in an S-shape, in a spiral shape, or in combination thereof.

[0052] By appropriately setting the irradiation conditions of the laser light, the type of the laser light, and the like, the degree of polyeneization and width of the polyene-containing portion, the thickness of the sealing portion, and the like can be adjusted.

[0053] In another embodiment, the manufacturing method includes irradiating the end face of the polarizing plate with an electron beam and then heating the irradiated portion. By such an operation, the polyene portion 40 and the sealing portion 50 can also be formed simultaneously. The electron beam can representatively irradiate the end face of the polarizing plate. The processing speed is preferably 1m / min to 10m / min, more preferably 2m / min to 5m / min. The beam current is preferably 5mA to 30mA, more preferably 12.5mA to 17.5mA. The efficiency coefficient K of electron beam irradiation is preferably 60 to 130, more preferably 80 to 120. The efficiency coefficient is a value determined by the acceleration voltage, but the correspondence between the acceleration voltage and the efficiency coefficient of each device is different. The dose of the electron beam is preferably 200kGy to 1000kGy, more preferably 250kGy to 500kGy. It should be noted that the dose D (kGy) is calculated by the following formula.

[0054] D=K×I / V

[0055] K: Efficiency coefficient

[0056] I: beam current (mA)

[0057] V: Processing speed (m / min)

[0058] The heating temperature is preferably 80° C. or higher, more preferably 90° C. to 130° C., and even more preferably 100° C. to 120° C. The heating time is preferably 10 hours or more, more preferably 15 hours to 30 hours, and even more preferably 22 hours to 26 hours. Under such heating conditions, a polyolefin portion having a desired degree of polyolefination and width and a sealing portion having a desired thickness can be formed.

[0059] C. Image display device

[0060] The polarizing plates described in the above items A and B can be applied to image display devices. Therefore, such image display devices are also included in the embodiments of the present invention. The image display device comprises: a display unit, and the polarizing plates described in the above items A and B arranged on at least one side of the display unit. As the image display device, for example, a liquid crystal display device and an organic electroluminescent (EL) display device can be cited. The structure of the image display device is well known in the industry, so a detailed description is omitted.

[0061] Example

[0062] Hereinafter, the present invention will be specifically described by way of Examples, but the present invention is not limited to these Examples.

[0063] [Example 1]

[0064] 1. Production of polarizer

[0065] As the thermoplastic resin substrate, a strip-shaped amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.

[0066] 13 parts by weight of potassium iodide were added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting product was dissolved in water to prepare a PVA aqueous solution (coating liquid).

[0067] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.

[0068] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).

[0069] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0070] Next, the polarizer was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the final polarizer would be a desired value (dyeing treatment).

[0071] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0072] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C and uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds to a total stretching ratio of 5.5 times.

[0073] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0074] Thereafter, the film was brought into contact with a SUS heating roll whose surface temperature was maintained at about 75° C. while being dried in an oven maintained at about 90° C. (drying shrinkage treatment).

[0075] In this way, a polarizer having a thickness of about 5 μm was formed on the resin substrate.

[0076] 2. Production of polarizing plate

[0077] With the help of ultraviolet curing adhesive, a cycloolefin film (ZEON, 17 μm) as a protective layer is bonded to the surface of the polarizer obtained above (the surface on the opposite side of the resin substrate). Specifically, the curing adhesive is applied in a manner that the total thickness is about 1.0 μm, and a roller press is used for bonding. Thereafter, UV light is irradiated from the cycloolefin film side to cure the adhesive. Next, an acrylic film (Toyo Steel Co., Ltd., 40 μm) is bonded to the surface of the polarizer exposed by peeling off the resin substrate in the same manner as above. In this way, a polarizing plate having the structure of cycloolefin film (protective layer) / polarizer / acrylic film (protective layer) is obtained.

[0078] 3. Formation of the polyene moiety

[0079] From the polarizing plate obtained by the above, a sheet-shaped polarizing plate of 50 mm × 50 mm size is cut out, wherein the polarizing plate has two opposite sides in the direction orthogonal to the stretching direction and the stretching direction. An electron beam irradiation device (manufactured by Iwasaki Electric Co., Ltd., product name "Standard EB Test Machine, Model: EC250 / 15 / 180L") is used to irradiate the end face of the cut polarizing plate with an electron beam. The irradiation conditions of the electron beam are: efficiency coefficient of 85, current of 15 mA, and processing speed of 3.9 m / min. In addition, the acceleration voltage at this time is 225 kV. Next, the polarizing plate is heated at 105°C for 24 hours to form a polyene portion at the end of the polarizer. The width of the polyene portion is 250 μm. It should be noted that the width of the polyene portion is measured based on an image taken using a microscope. As described above, a polarizing plate having a polyene portion is prepared.

[0080] 4. Determination of decolorization amount

[0081] Prepare two polarizing plates having polyene portions obtained as described above, and use them as test pieces. Use an adhesive to bond the two test pieces to both sides of an alkali-free glass plate of the same size, respectively, to produce a laminate of a visual recognition side test piece / glass plate / back side test piece as a substitute for an image display device. The visual recognition side test piece and the back side test piece are bonded to the glass plate in such a way that the absorption axes of their respective polarizers are orthogonal to each other. The image display device substitute is placed in an oven at 65°C and 90% RH for 240 hours for heating and humidification, and the discoloration state of the end of the polarizing plate (substantially a polarizer) after heating and humidification is studied using a microscope. Specifically, the size of the discoloration from the end of the polarizer is measured (discoloration amount: μm). As a microscope, MX61L manufactured by Olympus Corporation is used, and the discoloration amount is measured based on an image taken at a magnification of 10 times. As Figure 3 The larger amount of discoloration (a) from the end in the stretching direction and (b) from the end in the direction perpendicular to the stretching direction was taken as the discoloration amount.

[0082] [Example 2]

[0083] The polyene portion was formed as follows, and the same operation as in Example 1 was performed to produce a polarizing plate having a polyene portion. The width of the polyene portion was 30 μm. In addition, it was confirmed that a sealing portion was formed simultaneously with the formation of the polyene portion. The moisture permeability of the sealing portion was 18 g / m 2 / 24hr, the thickness was about 13 μm. The obtained polarizing plate was measured for discoloration in the same manner as in Example 1. The results are shown in Table 1.

[0084] (Formation of Polyene Moiety)

[0085] A 20 cm × 30 cm polarizing plate was prepared, and a pulsed laser was irradiated on the center of the polarizing plate, thereby cutting out a 50 mm × 50 mm sheet polarizing plate with two sides opposite to the stretching direction and the stretching direction. The laser irradiation conditions were: power of 85 W, pulse frequency of 15 kHz, and processing speed of 15 mm / s.

[0086] [Comparative Example 1]

[0087] A polarizing plate was prepared in the same manner as in Example 1 except that electron beam irradiation and subsequent heat treatment were not performed. No polyene portion was formed on the polarizing plate. The obtained polarizing plate was measured for decolorization in the same manner as in Example 1. The results are shown in Table 1.

[0088] [Comparative Example 2]

[0089] A polarizing plate was prepared in the same manner as in Example 1 except that the heat treatment after the electron beam irradiation was not performed. No polyene portion was formed on the polarizing plate. The obtained polarizing plate was measured for the amount of discoloration in the same manner as in Example 1. The results are shown in Table 1.

[0090] [Table 1]

[0091]

[0092] As is clear from Table 1, the Examples of the present invention can significantly suppress the amount of discoloration after the heating and humidification test by forming a polyene portion at the end of the polarizer. This is an excellent effect that is completely unexpected based on common technical knowledge in the industry.

[0093] Industrial Applicability

[0094] The polarizing plate according to the embodiment of the present invention can be suitably used in an image display device (for example, a liquid crystal display device, an organic EL display device, or a quantum dot display device).

[0095] Description of Reference Numerals

[0096] 10 polarizers

[0097] 20 1st protection layer

[0098] 30 Second protection layer

[0099] 40 Polyolefinization Department

[0100] 50 Sealing part

[0101] 100 polarizing plate

Claims

1. A method for manufacturing a sheet-shaped polarizing plate, The polarizing plate includes: a polarizer composed of a polyvinyl alcohol-based resin film containing a dichroic substance, and protective layers arranged on both sides of the polarizer. A polyene portion is formed at the end of the polarizer. The manufacturing method comprises the steps of irradiating an end face of a polarizing plate cut into a sheet with an electron beam and then heating the irradiated portion. The electron beam dose in the electron beam irradiation is 200 kGy to 1000 kGy, The heating temperature is 90° C. to 130° C., and the heating time is 15 hours to 30 hours.

2. The manufacturing method according to claim 1, wherein: The polyolefin portion is formed at a position 50 μm or more inward in the plane direction from the outer peripheral end of the polarizer.

3. The manufacturing method according to claim 2, wherein: The polyolefin portion is formed at a position 1000 μm or less inward in a plane direction from an outer peripheral end of the polarizer.

Citation Information

Patent Citations

  • Polarizing plate and its production

    JP2000338329A

  • Protective film for polarizer and its manufacturing method

    JP2001343529A

  • Manufacturing method of thin polarizing film

    JP2012073580A

  • Transparent film

    WO2001037007A1

  • Polarizer, polarizing plate, and method for producing the polarizer

    CN107430235A